Transcriptomic Profiling Revealed Plexin A2 Downregulation With Migration and Invasion Alteration in Dacarbazine-Treated Primary Melanoma Cells - Tyumentseva, Anna; Averchuk, Anton; Palkina, Nadezhda; Zinchenko, Ivan; Moshev, Anton; Savchenko, Andrey; Ruksha, Tatiana (Frontiers in Oncology, 2021)
Melanoma is highly heterogeneous type of malignant neoplasm that is responsible for the majority of deaths among other types of skin cancer. In the present study, we screened a list of differentially expressed genes in two primary, drug-naïve melanoma cell lines derived from patients with melanoma following treatment of the cells with the chemotherapeutic agent dacarbazine. The aim was to determine the transcriptomic profiles and associated alterations in the cell phenotype. We found the vascular endothelial growth factor A/vascular endothelial growth factor receptor 2, phosphoinositide 3-kinase/protein kinase B and focal adhesion signaling pathways to be top altered after dacarbazine treatment. In addition, we observed the expression levels of genes associated with tumor dissemination, integrin β8 and matrix metalloproteinase-1, to be diminished in both cell lines studied, the results of which were confirmed by reverse transcription-quantitative polymerase chain reaction. By contrast, plexin A2 expression was found to be upregulated in K2303 cells, where reduced migration and invasion were also observed, following dacarbazine treatment. Plexin A2 downregulation was associated with the promotion of migrative and invasive capacities in B0404 melanoma cells. Since plexin A2 is semaphorin co-receptor that is involved in focal adhesion and cell migration regulation, the present study suggested that plexin A2 may be implicated in the dacarbazine-mediated phenotypic shift of melanoma cells. We propose that the signature of cancer cell invasiveness can be revealed by using a combination of transcriptomic and functional approaches, which should be applied in the development of personalized therapeutic strategies for each patient with melanoma.